Geriatric Emergency Department Innovations: The Impact of Transitional Care Nurses on 30‐day Readmissions for Older Adults. (1st December 2019) - Dresden, Scott M.; Hwang, Ula; Garrido, Melissa M.; Sze, Jeremy; Kang, Raymond; Vargas‐Torres, Carmen; Courtney, D. Mark; Loo, George; Rosenberg, Mark; Richardson, Lynne
Abstract: Objectives: Transitional care nurse (TCN) care has been associated with decreased hospitalizations for older adults in the emergency department (ED). The objective of this study was to evaluate the association between TCN care and readmission for geriatric patients who visit the ED within 30 days of a prior hospital discharge. Methods: We studied a prospective cohort of ED patients aged 65 and older with an ED visit within 30 days of inpatient discharge. Patients with an Emergency Severity Index of 1 or prior TCN contact were excluded. Entropy balancing and logistic regression were used to estimate the average incremental effect of the TCN intervention on risk of admission during the index ED visit and within 30 days of prior discharge. Results: Of 6, 838 visits, 608 included TCN care. TCN patients had lower risk of readmission during the index ED visit at Mount Sinai Medical Center (MSMC), −10.1 percentage points (95% confidence interval [CI] = −18.5 to −2.7), and Northwestern Memorial Hospital (NMH), −17.3 percentage points (95% CI = −23.1 to −11.5), but not St. Joseph's Regional Medical Center (SJRMC), −2.5 percentage points (95% CI = −10.5 to 5.5). TCN patients had fewer readmissions within 30 days of prior hospital discharge at NMH, −16.2 percentage points (95% CI = −22.0 to −10.3), but not at MSMC, −5.6 percentage points (95% CI = −13.1 to 1.8), or at SJRMC, 0.5 percentage points (95% CI = −7.2 to 8.2). Conclusions: Transitional care nurse care in the ED after a prior hospitalization was associated with decreased readmission of older adults during the index ED visit at two of three hospitals, with sustained reduction for the entire 30‐day readmission window at one hospital. TCN interventions in the ED may decrease readmissions for geriatric patients in the ED; however, these results may be dependent on implementation of the program and availability of ED, hospital, and local resources for older adults.